Torque, myoeletric sygnal and heart rate responses during concentric and eccentric exercises in older men - Quitério, Robison José [UNESP]; Melo, Ruth C.; Takahashi, Anielle C. M.; Aniceto, Isabela A. V.; Silva, Ester; Catai, Aparecida M. (Associação Brasileira Pesquisa Pos-graduacao Fisioterapia-abrapg-ft, 2011)
Background: The literature reports that the eccentric muscular action produces greater force and lower myoelectric activity than the concentric muscular action, while the heart rate (HR) responses are bigger during concentric contraction. Objectives: To investigate the maximum average torque (MAT), surface electromyographic (SEMG) and the heart rate (HR) responses during different types of muscular contraction and angular velocities in older men. Methods: Twelve healthy men (61.7 +/- 1.6years) performed concentric (C) and eccentric (E) isokinetic knee extension-flexion at 60 degrees/s and 120 degrees/s. SEMG activity was recorded from vastus lateralis muscle and normalized by Root Mean Square-RMS (mu V) of maximal isometric knee extension at 60 degrees. HR (beats/min) and was recorded at rest and throughout each contraction. The data were analyzed by the Friedman test for repeated measures with post hoc Dunn's test (p<0.05). Results: The median values of MAT (N.m/kg) was smaller and the RMS (mu V) was larger during concentric contraction (C60 degrees/s=2.80 and 0.99; C120 degrees/s=2.46 and 1.0) than eccentric (E60 degrees/s=3.94 and 0.85; E120 degrees/s=4.08 and 0.89), respectively. The HR variation was similar in the four conditions studied. Conclusion: The magnitude of MAT and RMS responses in older men were dependent of the nature of the muscular action and independent of the angular velocity, whereas HR response was not influenced by these factors.

CONTEXTUALIZAÇÃO: A literatura refere que a ação muscular excêntrica produz maior força e menor atividade mioelétrica que a concêntrica, enquanto a resposta da frequência cardíaca (FC) é maior durante a contração concêntrica que durante a excêntrica. OBJETIVOS: Investigar as respostas de torque médio máximo (TMM), eletromiografia de superfície (EMGs) e FC durante diferentes tipos de contração muscular e velocidades angulares em homens idosos. MATERIAIS E MÉTODOS: Doze homens saudáveis (61,7±1,6 anos) realizaram flexões e extensões do joelho concêntrica (C) e excêntrica (E) em 60º/s e 120º/s. Registrou-se a atividade EMGs do músculo vasto lateral e normalizou-se pela RMS (µV) da extensão isométrica máxima do joelho em 60º. A FC (bpm) foi registrada em repouso e durante cada contração. Os dados foram analisados utilizando-se o teste de Friedman para medidas repetidas com post hoc de Dunn (p<0,05). RESULTADOS: Os valores médios de TMM (N.m/kg) foram menores e os de RMS (µV) foram maiores (p<0,05) nas contrações concêntricas (C60º/s=2,80 e 0,99; C120º/s=2,46 e 1,0) comparativamente com as excêntricas (E60º/s=3,94 e 0,85; E120º/s=4,08 e 0,89), respectivamente. Já a variação da FC foi semelhante nas quatro condições estudadas. CONCLUSÃO: A magnitude das respostas de TMM e RMS em homens idosos foi dependente da natureza da ação muscular e independente da velocidade angular, enquanto as respostas da FC não foram influenciadas por esses fatores.
Torque, sinal eletromiográfico e respostas da frequência cardíaca durante exercícios concêntrico e excêntrico em homens idosos
Keywords: elderly; heart rate; isokinetic; exercise; surface electromyography